Comparison of Technological Methods for Small Diameter Hole Perforation in Titanium Alloys - V. Grachev, Mikhail; ., . (International Journal of Engineering and Technology, 2018)
There is a huge number of methods for hole obtaining. In view of the fact that an increasing number of parts demand an increased accuracy and roughness in the obtained holes, especially concerning thin sheet parts, there is the need of research in this field. The main goal of the work is to establish the most optimal method for small-diameter hole obtaining in titanium alloys. The sheet of titanium alloy OT4-1 is studied with the thickness of 0.5 mm. At the same time, rigid tolerances are established both for the holes themselves and for their location. Drilling, laser treatment and electroerosion ("super drilling") were chosen as the drilling methods. Other methods were not considered due to the possibility of aperture rupture between holes and other profile distortions for the part and the holes. The most optimal modes of hole obtaining were selected. The productivity, the quality and the accuracy of the holes were evaluated. They studied in detail the technologies for the obtaining of holes with the purpose of processing mode setting. The main recommendations were presented for an optimal method selection concerning the obtaining of small diameter holes in thin-sheet titanium alloys.Â Â